2009
DOI: 10.1007/978-1-60327-811-9_10
|View full text |Cite
|
Sign up to set email alerts
|

High-Throughput Analysis of Serum Antigens Using Sandwich ELISAs on Microarrays

Abstract: Enzyme-linked immunosorbent assay (ELISA) microarrays promise to be a powerful tool for the detection and validation of disease biomarkers. ELISA microarrays are capable of simultaneous detection of many proteins using a small sample volume. Although there are many potential pitfalls to the use of ELISA microarrays, these can be avoided by careful planning of experiments. In this chapter we describe a high-throughput protocol for processing ELISA microarrays that will result in reliable and reproducible data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 12 publications
0
16
0
Order By: Relevance
“…Slides were printed using a piezoelectric GeSiM NanoPlotter 2 and processed as described previously (Servoss et al, 2009). All ELISA reagents for the 18 cytokine assays (amphiregulin (AMR), eotaxin, granulocyte-colony stimulating factor (GCSF), interleukins 1α, 6, and 12 (IL-1α, 6, and 12), GRO1 oncogene (KC; CXCL1), matrix metalloproteinase 2 (MMP2), small inducible cytokine A5 (RANTES; CCL5), thymus and activation-regulated chemokine (TARC; CCL17), tumor necrosis factor (TNFα), vascular endothelial growth factor A (VEGF), monocyte chemotactic protein 1 (MCP1), macrophage-derived cytokine (MDC), macrophage inflammatory proteins 1α (MIP-1α, CCL3), 1β (MIP-1β,CCL4), 1γ (MIP-1γ,CCL9) and 2 (MIP-2, CXCL2)) were purchased from R&D Systems.…”
Section: Methodsmentioning
confidence: 99%
“…Slides were printed using a piezoelectric GeSiM NanoPlotter 2 and processed as described previously (Servoss et al, 2009). All ELISA reagents for the 18 cytokine assays (amphiregulin (AMR), eotaxin, granulocyte-colony stimulating factor (GCSF), interleukins 1α, 6, and 12 (IL-1α, 6, and 12), GRO1 oncogene (KC; CXCL1), matrix metalloproteinase 2 (MMP2), small inducible cytokine A5 (RANTES; CCL5), thymus and activation-regulated chemokine (TARC; CCL17), tumor necrosis factor (TNFα), vascular endothelial growth factor A (VEGF), monocyte chemotactic protein 1 (MCP1), macrophage-derived cytokine (MDC), macrophage inflammatory proteins 1α (MIP-1α, CCL3), 1β (MIP-1β,CCL4), 1γ (MIP-1γ,CCL9) and 2 (MIP-2, CXCL2)) were purchased from R&D Systems.…”
Section: Methodsmentioning
confidence: 99%
“…Quantitative, multiplexed, sandwich ELISA microarray analysis was undertaken as described previously [17, 18]. We have previously demonstrated that the multiplexed assays used in the current study do not have any detectable cross-assay interference, and that this analytical platform can quantitatively detect purified antigens spiked into human sera [17].…”
Section: Methodsmentioning
confidence: 99%
“…Cell extracts containing the antigens were incubated on the chip and captured by the respective spotted antibodies. This step was followed by addition of labelled purified monoclonal antibodies recognising a different specific epitope of the antigen [59]. Avoidance of the labelling operation and achievement of specific signals were two important advantages associated with this assay.…”
Section: Antibody Microarray Assaysmentioning
confidence: 99%